Acoustics of the Orthodox Churches in Poland - MAŁECKI, Pawel; WICIAK, Jerzy; NOWAK, Damian (Archives of Acoustics, 2017)
An Orthodox church as a building expresses the Eastern Orthodox spirituality – all the details and general aspects have a deep and philosophical meaning. The architecture, being an illustration of the character of the Orthodox Church liturgy, has become a natural component of the cultural landscape of Poland and Eastern Europe. Acoustic research into Orthodox churches has so far been marginalized. Up to now, only a few churches of this type have been studied. The article is a review of the acoustic environment of churches in Poland. Churches, differing in terms of size, architectural style and other quantities, were chosen and acoustic measurements were made. The results of the measurements have been analyzed and collated. In particular, a detailed analysis and comparison was made for reverberation time as a function of frequency, due to the largest differences in this parameter between the rooms.